Integrated syphilis/HIV screening in China: a qualitative analysis - Yin Yue-Pin; Yang Bin; Zhu Zheng-Jun; Yang Li-Gang; Tucker Joseph D; Cohen Myron S; Chen Xiang-Sheng (BMC, 2010)
Abstract Background The last decade has seen enormous advances in HIV treatment and care, but how to implement scaled up HIV testing, prevention, and treatment in low-income areas still presents a formidable public health challenge. South China faces expanding syphilis and sexually transmitted HIV epidemics, but health systems characteristics important for scaling up syphilis and HIV testing have not been defined. Methods A purposive sample to ensure public, private, and public-private hybrid STI clinic inclusion was selected in a South China city. Eight key informant interviews were conducted with the STI clinic manager, followed by eight focus group discussions with physicians. Data collection relied on a semi-structured format that included questions in each of the following domains: 1) clinical facilities; 2) laboratory capacity with a focus on syphilis/HIV diagnosis; 3) clinic personnel; 4) physical space with a focus on locations to disclose confidential results; 5) financial support. Results Public STI clinics had free syphilis testing/treatment and laboratory facilities to perform essential syphilis and HIV tests. However, despite serving a large number of STI patients, private STI clinics lacked nontreponemal syphilis testing, HIV testing, and had fewer connections to the public health infrastructure. Formally trained assistant physicians were 2.5 times as common as physicians at STI clinics. Only one of the 8 sites had onsite voluntary counseling and testing (VCT) services available. Conclusion These STI case studies reveal the potential for expanding integrated syphilis/HIV services at public STI clinics in China. More health services research is needed to guide scale-up of syphilis/HIV testing in China.